2014
DOI: 10.1093/infdis/jiu832
|View full text |Cite
|
Sign up to set email alerts
|

Medroxyprogesterone Acetate Regulates HIV-1 Uptake and Transcytosis but Not Replication in Primary Genital Epithelial Cells, Resulting in Enhanced T-Cell Infection

Abstract: Although clinical and experimental evidence indicates that female sex hormones and hormonal contraceptives regulate susceptibility to human immunodeficiency virus type 1 (HIV-1) infection, the underlying mechanism remains unknown. Genital epithelial cells (GECs) are the first cells to encounter HIV during sexual transmission and their interaction with HIV may determine the outcome of exposure. This is the first report that HIV uptake by GECs increased significantly in the presence of the hormonal contraceptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 43 publications
4
45
1
Order By: Relevance
“…Previously, several studies had indicated that P 4 or its synthetic form increased HIV-1 susceptibility or risk of infection (Asin et al 2008, Ramjee & Wand 2012, Ferreira et al 2014) in a macaque model using subcutaneous implants of P 4 which increased vaginal SIV transmission several fold (Marx et al 1996). Similar to these earlier studies, we also observed that treatment with steroid hormones increased HIV-1 viral load levels in culture supernatants.…”
Section: Discussionsupporting
confidence: 89%
“…Previously, several studies had indicated that P 4 or its synthetic form increased HIV-1 susceptibility or risk of infection (Asin et al 2008, Ramjee & Wand 2012, Ferreira et al 2014) in a macaque model using subcutaneous implants of P 4 which increased vaginal SIV transmission several fold (Marx et al 1996). Similar to these earlier studies, we also observed that treatment with steroid hormones increased HIV-1 viral load levels in culture supernatants.…”
Section: Discussionsupporting
confidence: 89%
“…For example, in mice MPA at 4–7 nM decreases genital tract barrier function with an increased susceptibility to HSV-2 viral infection [59]. E x vivo data are broadly consistent with results from animal studies; MPA appears to increase HIV-1 proliferation in human immune cells at about 0.1 nM [72], dampen the function of immune cells at 0.3 nM [73], increase transcytosis of HIV-1 across the FGT epithelial cells at 1 nM [74], and decrease expression of select immunomodulators by FGT epithelial cells at 1–20 nM [74, 75]. The relative roles of the GR and PR in these mechanisms is not established, although MPA has been shown in vitro to regulate expression of immunomodulators and the function of immune cells via the GR [54, 7579].…”
Section: Dmpa-sc Vs Dmpa-im: Similar or Different Hiv Acquisition Rimentioning
confidence: 68%
“…Cells were also treated with amiloride, which inhibits macropinocytosis (Ivanov, 2008a; Saeed et al, 2010). These drugs are widely used for blocking endocytosis and macropinocytosis by many viruses, including HIV (Carter et al, 2011, 2009; Daecke et al, 2005; Dorosko and Connor, 2010; Ferreira et al, 2015; Grigorov et al, 2006; Kinlock et al, 2014; Liu et al, 2002; Mikulak et al, 2009; Miyauchi et al, 2009; Platt et al, 2014; Sloan et al, 2013). After 1 h of treatment, dual-tropic HIV-1 SF33 internalization was examined from the apical (AP) surface of epithelium by p24 ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…HIV-1 has been detected in the endosomes, MVB, and vacuoles of epithelial cells (Daecke et al, 2005; Dorosko and Connor, 2010; Ferreira et al, 2015; Grigorov et al, 2006; Kinlock et al, 2014; Mikulak et al, 2009; Orenstein, 2007; Tugizov et al, 2011; Yasen et al, 2017). However, critical extra- and intraepithelial molecules regulating vesicular trafficking of virions are still poorly investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation